Selected Lectures of the 17th International Workshop on Neonatology and Pediatrics, Virtual Edition; Cagliari (Italy); October 28-29, 2021 - Various Authors, --- (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2021)
SELECTED LECTURES OF THE 17TH INTERNATIONAL WORKSHOP ON NEONATOLOGY AND PEDIATRICS • VIRTUAL EDITION CAGLIARI (ITALY) • OCTOBER 28TH-29TH, 2021 LECT 1. PULSE OXIMETRY IN CRITICAL AND SEVERE CONGENITAL HEART DISEASE • A.C. Petropoulos, A. Charitou (Athens, Greece) LECT 2. MACRONUTRIENTS AND MICRONUTRIENTS THROUGH GROWTH AND DEVELOPMENT • G. Corsello, A. Corsello (Palermo and Milan, Italy) LECT 3. NEONATAL PERSISTENT PULMONARY HYPERTENSION: iNO FOR EVERYBODY? • S.G. Golombek (Valhalla, NY, USA) LECT 4. SLEEP DISTURBANCES IN THE NICU GRADUATE • D. Gozal (Columbia, MO, USA) LECT 5. CAN WE BETTER TAILOR SURFACTANT THERAPY IN 2021? • F. Mosca, A. Lavizzari (Milan, Italy) LECT 6. PRESEPSIN AND OTHER BIOMARKERS OF SEPSIS • M. Mussap (Cagliari, Italy) LECT 7. ENVIRONMENT, FETAL EPIGENETIC PROGRAMMING AND PREVENTION OF CHRONIC DISEASES • E. Burgio (Bruxelles, Belgium) LECT 8. BRONCHIOLITIS: LONG-TERM CONSEQUENCES • A. Dotta, S. Caoci, M. Calì, F. Savignoni (Rome, Italy) LECT 9. INTRAUTERINE GROWTH RESTRICTION: CLINICAL CONSEQUENCES ON HEALTH AT ADULTHOOD • J.B. Amengaud, U. Simeoni (Lausanne, Switzerland) LECT 10. NEONATOLOGY: A YOUNG SCIENCE • G. Buonocore (Siena, Italy) LECT 11. WHAT IS NEXT FOR PEDIATRICS AFTER COVID-19? • A. Staiano (Naples, Italy) LECT 12. CLINICAL FEATURES OF CHILDREN AND ADOLESCENTS WITH COVID-19: THE EXPERIENCE OF A TERTIARY PEDIATRIC HOSPITAL • M. De Filippo, M. Votto, F. Giffoni, V. Santi, M. Vergani, A. Licari, G.L. Marseglia (Pavia, Italy) LECT 13. WEANING: FROM RESPONSIVE FEEDING TO MODULATION OF CHILDREN’S FOOD PREFERENCES • A. Bosco, A. Dessì (Cagliari, Italy) LECT 14. MICROBIOME, METABOLOMICS AND WEANING DIET: WHAT IS THE CORRELATION? • A. Dessì, A. Bosco (Cagliari, Italy) LECT 15. THORACIC ULTRASOUND IN NEWBORNS • L. Capasso, F. Migliaro, S. Salomè, C. Veropalumbo, C. Colinet, D. Lucignano, F. Raimondi (Naples, Italy) LECT 16. PERINATAL ASPHYXIA: NEW EVIDENCE, WHAT WE KNOW, WHAT WE DO NOT KNOW • G. Ancora (Rimini, Italy) LECT 17. IUGR AND NEUROLOGICAL OUTCOME • M. Vendemmia, C.V. Lambiase, G. Mansi, F. Raimondi (Naples, Italy) LECT 18. RETINOPATHY OF PREMATURITY • C. Dani (Florence, Italy) LECT 19. PEDIATRIC ASTHMA MANAGEMENT DURING COVID-19 TIMES • C. Capristo (Naples, Italy) LECT 20. CHARACTERISTICS OF SARS-CoV-2 INFECTION IN CHILDREN • D.A. Plesca (Bucharest, Romania) LECT 21. WHICH FUTURE FOR CHILDREN AND ADOLESCENTS AFTER COVID-19 • G. Perricone (Palermo, Italy) LECT 22. THE FIRST THOUSAND DAYS OF LIFE: THE ROLE OF THE MICROBIOTA • V. Fanos, R. Pintus (Cagliari, Italy) LECT 23. THE FIRST THOUSAND DAYS OF LIFE: FROM THE PLACENTA TO NEURODEVELOPMENT • V. Fanos, S. Angioni, E. Burgio, I. Cetin, A. Dessì, M. D’Alterio, A. Distante, G. Faa, A. Falco, G. Fedrizzi, O. Forleo, F. Cesare Marincola, M. Mauri, L. Migliore, C. Novielli, R. Pintus, M. Piras, S. Schirru, S. Stagno, A. Stoccoro (Cagliari, Brindisi, Milan, Bologna, Taranto and Pisa, Italy) LECT 24. BIFIDOBACTERIA AS BIOMARKERS OF THE BABY’S GUT HEALTH • M. Romeo (Milan, Italy)